Study of the Effect of Methyl Jasmonate Concentration on Aflatoxin B1 Biosynthesis by Aspergillus parasiticus in Yeast Extract Sucrose Medium - Dido Maria Meimaroglou; Dia Galanopoulou; Panagiota Markaki (International Journal of Microbiology)
Aflatoxin B1 (AFB1) is a carcinogenic metabolite produced by certain Aspergillus species on agricultural commodities. AFB1 biosynthesis is affected by jasmonic acid and also by its methylester (MeJA), a plant growth regulator derived from linoleic acid. This study reports the effect of MeJA on the growth of A. parasiticus and AFB1 output in yeast extract sucrose (YES) medium when added at three different concentrations; namely, 10−2 M, 10−4 M, and 10−6 M. AFB1 determination was performed by immunoaffinity and HPLC. MeJA at 10−4 and 10−6 M concentrations had no significant effect on mycelial growth but did affect AFB1 production after the 7th day of incubation; on the 12th day, AFB1 production was increased by 212.7% and 141.6% compared to the control samples (addition of 10−6 M and 10−4 M MeJA, resp.). Treatment of A. parasiticus cultures with 10−2 M MeJA inhibited mycelial growth and AFB1 production as well. These results suggest that the effect of MeJA on AFB1 biosynthesis by A. parasiticus depends on the MeJA concentration used.